Corporate Globalization and Worker Representation - Uwe Jirjahn (Institute of Labor Economics (IZA), 2024)
This chapter reviews research on the linkages between corporate globalization and worker representation. Studies have identified various transmission channels through which the activities of foreign multinational companies (MNCs) affect host-country institutions of union and non-union representation. First, countries compete for inbound foreign direct investment (FDI) and the ability to attract FDI depends among others on a country's industrial relations system. Second, once foreign MNCs have invested in a host country, they exert an influence on the country's institutions of worker representation through how their affiliates adapt to those institutions or tend to avoid them. Third, the affiliates of foreign MNCs affect the bargaining power of host-country worker organizations. Fourth, foreign affiliates have an impact on labor conflicts and the quality of industrial relations. Altogether, the available evidence provides indications that the activities of foreign MNCs can be a challenge for worker representation within host countries.
Keywords: F23; F66; J51; J52; J53; J83; 330; multinational company; foreign direct investment; union avoidance; bargaining power; labor conflict; centralized bargaining; works council